Використання видів і форм Carpinus L. у зеленому будівництві - Ishchuk, L.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
Ornamental properties of species and forms of Carpinus L and their use in landscape architecture are described as based on the data from literature and the author’s observations. Practical recommendations on planting hornbeam trees in the form of avenues, solitaires, spinneys, hedgerows and other topiary constructions are presented in the paper.